The future organisation of banking ... lectures. (Edinburgh : Published for the Institute of Bankers in Scotland by W. Blackwood, 1958)
If this book contributes something to the education and training of bankers who will have to face the problems of the second half of the twentieth century, it and the summer school 1958 will have served their purpose.
Bibliography: p. 93.
osc 7/5/18
Loans
Keywords: Banks and banking